Edukasi Masyarakat Terkait Diabetes Mellitus, Pencegahan, dan Terapi Komplementer dengan Teh Putih (Camellia sinensis L.) dan Probiotik (Lactiplantibacillus plantarum) di Desa Babelan Kota Kabupaten Bekasi: The Health Education Regarding Diabetic Mellitus, Prevention, and Complementer Therapy with White Tea (Camellia sinensis L.) and Probiotic (Lactiplantibacillus plantarum) at Desa Babelan Kota, Bekasi District - Zahara, Indah; Ekayanti, Meiliza; Setiadi, Feri; Alfianna, Wiwin; Rizki, Yulia Rafitri (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The prevalence of Diabetes Mellitus (DM) has consistently increased and is one of the main death issues in the world due to complications. The increase in Diabetes cases in Bekasi Regency was 38% since 2020. Educational programs aim to increase awareness and reduce DM cases in Bekasi Regency. The method was direct (seminar) and indirect (media) and questionnaires to determine knowledge. The total of participants was 22 (male 55% and female 45%), and the largest age group was 46-55 years (54.5%). The average knowledge pre-education (77,3%) and post-education (81,3%) are categorized as “good”. The result of the analysis using T-test sig. value (2-tailed) obtained 0.000 (α<0,005). It was concluded there was an influence on the level of knowledge of participants pre- and post-education.